Comparative Analysis of the Chalcone-Flavanone Isomerase Genes in Six Citrus Species and Their Expression Analysis in Sweet Orange (Citrus sinensis) - Wan, Quan; Bai, Tingting; Liu, Minmin; Liu, Ying; Xie, Yating; Zhang, Tao; Huang, Min; Zhang, Jinlian (Frontiers in Genetics, 2022)
Citrus fruit contains rich nutrients which is edible and officinal value. Citrus flavanones are widely used in the treatment of cardiovascular and other diseases, and it is a foundational material of Chinese medicine. The chalcone--flavanone isomerase (CHI) plays a key role in flavanones synthesis. Therefore, we comprehensively analysed CHI genes in Citrus species. Here, Thirty CHI genes were identified for the first time in six Citrus species, which were divided into CHI and FAP groups. Evolutionary analysis showed that CHI gene members were highly conserved, and was an ancient family. All CsCHI genes showed the highest expression level after the second physiological fruit-falling period in C. sinensis. CsCHI1 and CsCHI3 were highly expressed at 50DAF stage in albedo. The expression of CsFAP2 and CsCHI3 genes at 50DAF stage were 16.5 and 24.3 times higher than that at 220DAF stage, respectively. The expression of CsCHI1, CsCHI3 and CsFAP2 genes in peel was higher than that in pulp, especially in common sweet orange. CsCHI3 gene maintained a high expression level in epicarp and juice sac at any periods. The members of CHIs interacted with TTS, F3H and FLS to form heterodimers, might play a regulatory role together and participated in flavonoids pathway. This study will provide the basis for the selection of flavonoids in plant tissues and periods and fundamental information for further functional studies.